The Importance of Early Intervention: A Systematic Literature Review on the Environment Impact on Early Childhood Development - Agustin, Hanum Widyanti; Nur, Lutfi; Purwati, Purwati (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
The importance of early childhood as a critical period for the development of children’s physical, cognitive, social, and emotional abilities cannot be overstated. This phase is significantly influenced by various environmental factors, including family, community, and physical surroundings. However, the reality in the field highlights disparities in the quality of environments experienced by children, particularly in areas with limited economic resources or access to educational and healthcare facilities. This study aims to analyze the influence of the environment on early childhood development. It employs the Systematic Literature Review (SLR) method, a specific research methodology used to collect and evaluate various studies relevant to the research focus. In this study, the researcher examines 10 topics related to the research title. The environment has a significant impact on early childhood development, as this stage involves rapid physical, cognitive, emotional, and social growth in children.